Targeting Human Thrombus by Liposomes Modified with Anti-Fibrin Protein Binders - Petroková, Hana; Mašek, Josef; Kuchař, Milan; Vítečková Wünschová, Andrea; Štikarová, Jana; Bartheldyová, Eliška; Kulich, Pavel; Hubatka, František; Kotouček, Jan; Knotigová, Pavlína Turánek; Vohlídalová, Eva; Héžová, Renata; et al. (Pharmaceutics, 2019)
Development of tools for direct thrombus imaging represents a key step for diagnosis and treatment of stroke. Nanoliposomal carriers of contrast agents and thrombolytics can be functionalized to target blood thrombi by small protein binders with selectivity for fibrin domains uniquely formed on insoluble fibrin. We employed a highly complex combinatorial library derived from scaffold of 46 amino acid albumin-binding domain (ABD) of streptococcal protein G, and ribosome display, to identify variants recognizing fibrin cloth in human thrombus. We constructed a recombinant target as a stretch of three identical fibrin fragments of 16 amino acid peptide of the Bβ chain fused to TolA protein. Ribosome display selection followed by large-scale Enzyme-Linked ImmunoSorbent Assay (ELISA) screening provided four protein variants preferentially binding to insoluble form of human fibrin. The most specific binder variant D7 was further modified by C-terminal FLAG/His-Tag or double His-tag for the attachment onto the surface of nanoliposomes via metallochelating bond. D7-His-nanoliposomes were tested using in vitro flow model of coronary artery and their binding to fibrin fibers was demonstrated by confocal and electron microscopy. Thus, we present here the concept of fibrin-targeted binders as a platform for functionalization of nanoliposomes in the development of advanced imaging tools and future theranostics.
Keywords: ABD scaffold; liposome; thrombus imaging; binding protein; thrombus targeting; fibrin; combinatorial library; fibrinogen Bβ chain; metallochelation